2014
DOI: 10.1530/erc-14-0077
|View full text |Cite
|
Sign up to set email alerts
|

miR-145 suppresses thyroid cancer growth and metastasis and targets AKT3

Abstract: The expression and function of miR-145 in thyroid cancer is unknown. We evaluated the expression and function of miR-145 in thyroid cancer and its potential clinical application as a biomarker. We found that the expression of miR-145 is significantly downregulated in thyroid cancer as compared with normal. Overexpression of miR-145 in thyroid cancer cell lines resulted in: decreased cell proliferation, migration, invasion, VEGF secretion, and E-cadherin expression. miR-145 overexpression also inhibited the PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 48 publications
6
75
0
1
Order By: Relevance
“…In this study, we detected the expression of AKT3 in CRC and found that it was significantly upregulated. Notably, AKT3 has been found to be regulated by several miRNAs, such as miR-29a, miR-338-3p and miR-145 [3234]. To further verify whether AKT3 was a target gene of miR-384 in CRC, luciferase reporter assay, qRT-PCR, and western blot were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we detected the expression of AKT3 in CRC and found that it was significantly upregulated. Notably, AKT3 has been found to be regulated by several miRNAs, such as miR-29a, miR-338-3p and miR-145 [3234]. To further verify whether AKT3 was a target gene of miR-384 in CRC, luciferase reporter assay, qRT-PCR, and western blot were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that the PI3K/Akt pathway regulates the epithelial-mesenchymal transition, cell cycle, angiogenesis and apoptosis, and has an important role in tumor progression (26)(27)(28). The PI3K/Akt pathway was reported to be activated in PTC and to be involved in cell proliferation and migration (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, Kent et al (23) observed that RREB1 can inhibit the expression of miR-145. In addition, studies have demonstrated that miR-145 can inhibit the phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway through regulating the expression of integrin-linked kinase (24,25).…”
Section: Discussionmentioning
confidence: 99%